Dekonstruksi Otoritarianisme Hermeneutis Khaled Abou El Fadl: Relevansi Dan Implikasi Etis pada Moderasi Beragama di Indonesia - Anselmus Dore Woho Atasoge; Dominikus Doni Ola (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2026)
This research aims to deconstruct Khaled Abou El Fadl's hermeneutical framework and analyze its methodological relevance in responding to the dynamics of sacred text interpretation in Indonesia. The phenomenon of interpretive authoritarianism frequently triggers socio-religious polarization, necessitating accountable epistemological instruments. Employing a qualitative method through critical textual analysis of the monumental work Speaking in God’s Name, this study dissects the pathology of